The Critical Role of Official Qualifications in Maintaining Position Integrity from a Variety of Perspectives - Asmadun Asmadun; Taufiqurachman Taufiqurachman (STAATSRECHT: Indonesian Constitutional Law Journal, 2021)
The position of village officials is currently being targeted by many people with various educational backgrounds. Not only high school graduates or equivalent. Not even a few scholars are competing to get a strategic position in the village government apparatus. This study uses a qualitative approach. The results of the study state that village government positions are very important in the course of a country. This is because the village government is a component or a small part of the running of the government. The integrity and qualifications of village level officials from a legal point of view need to be continuously improved, due to the condition of uneven educational standards in village management.